Management of cardamom borer, Conogethes punctiferalis Guenee and thrips, Sciothrips cardamomi Ramk using diafenthiuron and its residues in fresh and cured cardamom capsules. Issue 2 (3rd April 2019) - Stanley, J.; Chandrasekaran, S.; Preetha, G.; Kuttalam, S.; Jasmine, R.S.
ABSTRACT: Cardamom is an important spice crops used all over the world as a flavoring agent of food materials. The productivity is limited by insect pests and thus effective insecticide which does not leave residues in the produce is the need of the hour. Diafenthiuron 50 WP @ 300 g a.i ha −1 was found effective in managing both the cardamom shoot and capsule borer, Conogethes punctiferalis Guenee and thrips, Sciothrips cardamomi Ramk and thus can be recommended for pest management. Cardamom capsules were collected from the plants that were sprayed with diafenthiuron at the recommended dose of 200 g a.i ha −1 and double the dose (400 g a.i ha −1 ), which were then analyzed under HPLC with a normal phase column. The diafenthiuron residue was below the detectable levels of 0.05 µg g −1 in the harvested produce (both fresh and cured) after twelve and fourteen days of spray. So, capsules can be harvested safely without any risk of insecticide residues 12 days after spraying of diafenthiuron and thus can be recommended for usage in cardamom plantations.